Термодинамические параметры геотермальной электрической станции с бинарным сверхкритическим циклом - Редько, А. А. (НТУ "ХПИ", 2009)
The design-theoretical research results of thermodynamic parameters for supercritical cycles of geothermal electric power plants are presented. The numerical results show the 10–13 % increase of cycles thermodynamic effectiveness with application of the ozone-safe freons and their mixtures as working mediums of plants for the geothermal water temperature of 100–130 °C.
Keywords: топливо; энергетическое оборудование; геотермальная энергия; геотермальная вода; мощность; критическая температура